2022
DOI: 10.1097/jnc.0000000000000342
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives About Transition Readiness Among Adolescents and Young People Living With Perinatally Acquired HIV in Rural, Southwestern Uganda: A Qualitative Study

Abstract: Despite the availability of antiretroviral therapy, treatment outcomes are worse among adolescents and young adults living with perinatally acquired HIV (AYLPHIV). These disparities are magnified during the transition from pediatric to adult-based HIV care. We conducted in-depth interviews with AYLPHIV aged 15-24 years (n 5 30), their caregivers (n 5 10), and health care providers (n 5 10). All participants provided written assent and/or informed consent to enroll. Thematic content analysis was used to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…Having a stable source of income has been associated with transition readiness among AYLPHIV [ 66 ] while economic empowerment has been associated with improved HIV treatment outcomes among AYLPHIV [ 17 , 67 ]. Finally, the informational support needed entails comprehensive knowledge of HIV, HIV transmission, and the role of ART adherence [ 68 , 69 ], as well as sexual and reproductive health [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a stable source of income has been associated with transition readiness among AYLPHIV [ 66 ] while economic empowerment has been associated with improved HIV treatment outcomes among AYLPHIV [ 17 , 67 ]. Finally, the informational support needed entails comprehensive knowledge of HIV, HIV transmission, and the role of ART adherence [ 68 , 69 ], as well as sexual and reproductive health [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Empowerment was viewed by participants as a necessary precondition for successfully transitioning to HIV care. Prior work has linked better outcomes to self-advocacy [51,69,[71][72][73][74][75], HIV status disclosure [11,66,[76][77][78][79][80], interpersonal skills [81][82][83], and self-care [50,[84][85][86]. AYPLHIV should be empowered with skills to enable them participate effectively in their care including making decisions related to their care, collaborating effectively with health care providers as they grow towards independence and assuming responsibility for their own HIV care [68].…”
Section: Discussionmentioning
confidence: 99%
“…Our discussions showed that successful transition included caregivers engaging adolescents in the process, including obtaining their assent to disclose their HIV status to school leadership, and caregivers actively assuming the role of transition-facilitators, by linking adolescents to school nurses. This process parallels some of the work already being done in Africa to support youth living with HIV as they transition to adult HIV care, where best practices include equipping adolescents with relevant information about their condition, self-advocacy skills, and support from caregivers [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Para asegurar una transición exitosa, es indispensable el cumplimiento de cada uno de los pasos anteriormente citados, con el objetivo de lograr un concepto de salud integral del adolescente (35). Gran parte de la literatura disponible describe el proceso de transición en patologías específicas (diabetes, virus de inmunodeficiencia humana, enfermedad reumatológica, enfermedades mentales entre otras) y muestran la experiencia de cada grupo enfocado e individualizado a cada enfermedad, cada una de las patologías muestran barreras específicas que se deben afrontar (36)(37)(38). Esto es un paso crucial y de gran importancia para la vida del adolescente (39).…”
Section: Lista De Chequeo Para Una Valoración Integral Durante La Tra...unclassified